PENGARUH APLIKASI MONITORING HIPERTENSI (MH) TERHADAP PENGETAHUAN TENTANG HIPERTENSI DAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Faridah , Ida; Afiyanti , Yati; Aditama, Dicky (Nusantara Hasana Journal, 2021)
Hypertension is a serious condition and can increase the risk of heart, brain, kidney, and other diseases. Hypertension is the leading cause of premature death worldwide with 1 in 4 men and 1 in 5 women, more than 1 billion people experiencing the condition. Hypertension monitoring application (MH) is expected to control hypertension and increase knowledge in hypertensive patients. Objective: This study aims to examine the effect of hypertension monitoring application on knowledge of hypertension and blood pressure in hypertensive patients. Research design: quasi-experimental (Pre and Post Test without control). Data analysis: Data analysis in this study used univariate and bivariate analysis. Results: From the results of the intervention to 99 respondents, the average value of the pre test and the post testÂ  with a value (P value) <0.05. Conclusion: There is a significant effect of the Hypertension Monitoring Application (MH) on Knowledge About Hypertension and Blood Pressure in Hypertensive Patients in Tangerang Raya. Â